The Application of Profile Matching Method in Determining Achieving Students at STMIK KHARISMA Makassar - Yeni Saharaeni; Husni Angriani (STMIK KHARISMA Makassar, 2026)
Student achievement was one of the primary considerations for scholarship recommendations and the selection of outstanding students at STMIK KHARISMA Makassar. However, the selection process was conducted manually through stakeholder meetings, making the assessment susceptible to subjectivity because it mainly relied on grade point average and organizational participation. This study aimed to develop a decision support system using the Profile Matching method to improve the objectivity of the selection process. The evaluation was based on four main criteria, namely grade point average, attitude, organizational experience, and parents' data, while organizational experience included participation in student activities, academic and non-academic achievements, promotional activities, and community involvement. The results showed that the determination of the ideal standard value, Core Factor, and Secondary Factor significantly influenced the final ranking. The Profile Matching method provided a more systematic, objective, and transparent approach for selecting outstanding students and recommending scholarship recipients.